(untitled) (Journal of Philosophy Culture and Political Science, 2018)
This article deals with the formation of the ethnic group and the stages of its formation in the course of history. These questions will be considered in historical terms, because the story is not a private phenomenon, and not similar to each other historical stages. The formation of the Kazakh nation define the terms: terms of material conditions of life, especially the economy, culture, social background, ethnic features. The concepts of «ethnics», «ethnic matching» includes everyday vocabulary of social and cultural anthropology and political science. The term «ethnics» is derived from the term «ethnic» and synonymous with «people», «kind», «nation», «nationality». «Ethnicity» – a community of people who live in a particular area, have a common language, and traditions. Key words: ethnicity, ethnic, ethnic line, community, nation, race, nation, the process of globalization, identity, spirituality, common language, tradition.